2008
DOI: 10.1002/jcla.20241
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dehydrogenase (ADH) isoenzymes and aldehyde dehydrogenase (ALDH) activity in the sera of patients with liver cancer

Abstract: The principal enzymes catalyzing the conversion of ethanol to acetate are alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH). The activities of these enzymes are elevated in the serum during the course of alcoholism or cirrhosis. In previous investigations we have found elevated levels of ADH, ALDH, and class I ADH activity in liver cancer cells. It can suggest that these changes may be reflected by enzyme activity in the serum. In this work, the activity of ADH isoenzymes, and ALDH in the sera of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 18 publications
0
40
1
2
Order By: Relevance
“…Many of these proteins were involved in cellular metabolism while a number were cytoskeletal proteins. Several of these proteins have also been reported to be differentially expressed in either hepatocellular carcinoma or other tumor types, for example alcohol dehydrogenase and aldehyde dehydrogenase [12], carbamyl phosphate synthase [13], selenium binding protein 1 and DNA helicase RuvB-like protein 2 ( [14][15][16]). …”
Section: Proteins Under-expressed In the Tumoral Liver Tissue Comparementioning
confidence: 99%
“…Many of these proteins were involved in cellular metabolism while a number were cytoskeletal proteins. Several of these proteins have also been reported to be differentially expressed in either hepatocellular carcinoma or other tumor types, for example alcohol dehydrogenase and aldehyde dehydrogenase [12], carbamyl phosphate synthase [13], selenium binding protein 1 and DNA helicase RuvB-like protein 2 ( [14][15][16]). …”
Section: Proteins Under-expressed In the Tumoral Liver Tissue Comparementioning
confidence: 99%
“…ALDH are a group of enzymes catalyzing the oxidation of acetaldehyde and transforming it into acetate [27]. Abnormal activity of ALDH is implicated in a variety of cancers such as lung, colorectal and breast cancer [28][29][30].This study indicated ALDH is involved in prolactinoma as well, and might be a possible biomarker for this disease. Besides, SNARE interactions in vesicular transport was "partially" enriched in protein complex 2, which was also associated with hormone secretion [31].…”
Section: Discussionmentioning
confidence: 74%
“…and need to be detoxified, as reviewed by Marchitti et al [16] . In addition to their important function in aldehyde detoxification, ALDHs perform other functions including ester hydrolysis, serving as binding proteins for various molecules (e.g., androgen and cholesterol) and potentially function as antioxidants by NAD(P) H production, ultra violet light absorption and/or hydroxyl radical scavenging [16,20,21] . Alcohol dehydrogenase and Aldehyde dehydrogenase which are most abundant in the liver, are the main enzymes involved in ethanol and acetaldehyde metabolism.…”
Section: Resultsmentioning
confidence: 99%